1994
DOI: 10.1002/cne.903440303
|View full text |Cite
|
Sign up to set email alerts
|

Localization and regulation of low affinity nerve growth factor receptor expression in the rat olfactory system during development and regeneration

Abstract: Nerve growth factor (NGF), a classic neurotrophic factor, promotes neuronal survival, maintenance, regeneration and differentiation in the peripheral nervous system and parts of the central nervous system. NGF activity is mediated by cell surface bound receptors including the low affinity NGF receptor (LNGFr) which is expressed by some peripheral and central neurons and is present on peripheral nerve Schwann cells during development and regeneration. The olfactory system is a useful model for the study of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 68 publications
8
88
0
Order By: Relevance
“…NT R [20,23,61] and S-100 protein [3,44]. In this study double staining with anti-S-100 and Nuclear Yellow (Sigma, St. Louis, MO) was randomly performed in different batches to ascertain the high purity of EC cultures which has been consistently obtained in earlier studies (Fig.…”
Section: Olfactory Ensheathing Cell Culturementioning
confidence: 94%
“…NT R [20,23,61] and S-100 protein [3,44]. In this study double staining with anti-S-100 and Nuclear Yellow (Sigma, St. Louis, MO) was randomly performed in different batches to ascertain the high purity of EC cultures which has been consistently obtained in earlier studies (Fig.…”
Section: Olfactory Ensheathing Cell Culturementioning
confidence: 94%
“…Perhaps very fine processes of olfactory nerve Schwann cells might not have been labeled for S-100 protein or detected in our study. Alternatively, species differences might exist: Gong et al (1994) in studies of the rat also indicated that somata and processes of olfactory nerve Schwann cells remain within the nerve layer. Olfactory nerve Schwann cells might constrain mitral cell dendrites by forming a mechanical border or by emitting chemorepulsive cues.…”
Section: Spatial Relationships Between Mitral Cell Dendrites and Olfamentioning
confidence: 95%
“…S100 is useful as a marker for the olfactory ensheathing cells (OECs) of the ONL-o, 9,10,12 and p75 is positive in the OECs of the ONL-o, the glomeruli, and glial cells of the GL from late embryonic stages to adult stages. 10,13 Although GFAP is expressed in the astrocytes of the ONL-i and the GL during postnatal stages, 11,14 it has been reported that GFAP is also contained in OECs of the ONL. 15,16 TROY was highly observed in the ONL-i and was colocalized with GFAP in the GL and the ONL-i and with p75 in some glial cells of the GL of adult mice.…”
Section: Characterization Of Troy-expressing Cells In the Developing mentioning
confidence: 99%